PANARCHY BY DESIGN: CROSS-SCALE ADAPTIVE ENVIRONMENTAL LAW FOR A TURBULENT CLIMATE - Fitrilya Anjarsari (Faculty of Law Atma Jaya Yogyakarta University, 2026)
This article develops a panarchy-informed blueprint for cross-scale adaptive environmental law under climate turbulence, using panarchy to explain how nested adaptive cycles and thresholds across scales can cause policies that work locally to fail at provincial or national levels, and vice versa. It asks: (1) how statutes can learn across scales without eroding legal certainty or equity; and (2) which design elements enable timely, evidence-based adjustment under climate volatility. Methodologically, the study integrates doctrinal analysis of statutes, regulations, and review practices with comparative case studies of watersheds, forests, and coastal zones, combining system mapping of feedback loops and decision interfaces with process tracing of revision episodes and, where data allow, interrupted time-series evaluation to assess policy timing and effects. Across cases, it evaluates three performance metrics: ecological fit, adaptation lead time, and distributive impact, and finds that robust adaptive capacity increases when learning loops are nested, transparent, and institutionally constrained. The article proposes a modular drafting toolkit comprising threshold-based legal triggers tied to ecological indicators, periodic review with ratchet and sunset clauses, subsidiarity with upward and downward escalation rules, mandatory open-data pipelines, and enforceable safeguards for Indigenous and marginal communities, translating panarchy into actionable legal design principles for accountable adaptation.